Analysis of Teachers' Specific Readiness in An In-Depth Approach to Islamic Education Learning - Cahyati, Putri; Elvita, Yanti; Ilahi, Wahyu; Ramli, Syahrur; Rusdi, Luthfia Fadhila; Rosalina, Viona (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This study aims to analyze the specific readiness of Islamic Religious Education (PAI) teachers in implementing the deep learning approach within the Independent Curriculum. The main issue addressed in this study is the gap between teachers’ mastery of religious content (tafaqquh fiddin) and their ability to design innovative pedagogical strategies that encourage inquiry-based learning, such as projects on Religious Moderation. This research employs a qualitative approach with a phenomenological design. The participants of this study were 12 PAI teachers from several senior high schools in Tanah Datar, West Sumatra. Data were collected through in-depth interviews, participatory observation, and document analysis. The data were analyzed using thematic analysis techniques. The findings show that teachers who successfully implement deep learning approaches are those who are able to negotiate their professional identity between maintaining religious traditions and acting as agents of pedagogical innovation. These teachers are capable of integrating the authority of religious texts with students’ critical experiences in the learning process. The study highlights the importance of strengthening Subject-Specific Teacher Readiness and Spiritually-Engaged Pedagogical Reasoning in order to support authentic teacher readiness in Islamic education.